ANALISIS EFFICIENCY PERBANKAN DI NEGARA ASEAN TAHUN 2006 – 2020 - Sugiarto, Mohammad Abdurrahman Alkhadaqi (Program Studi Ekonomi Pembangunan, 2022)
This study aims to find out the efficiency of banking in asean countries as measured in indicators: Bank Indonesia the central bank/bi decided to raise its benchmark interest rate by 25 basis points to 8.25 percent in the second quarter of 2008 to 8.25 percent in the second quarter of this year. The data used in this study took from the world bank website as well as the financial services authority with a sample of nine Banks in asean state. The method of analysis used in this study uses multiple regression analysis. The results on this study are CAR significant positive effects on ROA, LDR has significant positive effects on roa, BOPO has significant negative effects on ROA, PE has insignificant positive effects on ROA, INF has significant positive effects on ROA.